Laparoscopic adrenalectomy in urological centres: the experience of the German Laparoscopic Working Group - Greco, Francesco; Hoda, M. Raschid; Rassweiler, Jens; Fahlenkamp, Dirk; Neisius, Dietmar A.; Kutta, Andreas; Thüroff, Joachim W.; Krause, Andreas; Strohmaier, Walter L.; Bachmann, Alexander; Hertle, Lothar; Popken, Gralf; et al. (BJU international, 2011)
Study Type - Practice patterns (retrospective cohort) Level of Evidence 2b OBJECTIVE • To evaluate the safety and feasibility of laparoscopic adrenalectomy (LA) performed in several German centres with different laparoscopic experience, as LA has become the gold-standard approach for benign surgical adrenal disorders; however, for solitary metastasis or primary adrenal cancer its precise role is uncertain. PATIENTS AND METHODS • The data of 363 patients who underwent a LA were prospectively collected in 23 centres. • All centres were stratified into three groups according to their experience: group A (<10 LAs/year), group B (10-20 LAs/year) and group C (>20 LAs/year). • In all, 15 centres used a transperitoneal approach, four a retroperitoneal approach and four both approaches. • Demographic data, perioperative and postoperative variables, including operating time, surgical approach, tumour size, estimated blood loss, complications, hospital stay and histological tumour staging, were collected and analysed. RESULTS • The transperitoneal approach was used in 281 cases (77.4%) and the retroperitoneal approach was used in 82 patients (22.6%). • In all, 263 of 363 lesions (72.5%) were benign and 100 (27.5%) were malignant. • The mean (sd) operating time was 127.22 (55.56) min and 130.16 (49.88) min after transperitoneal and retroperitoneal LA, respectively. • The mean complication rates for transperitoneal and retroperitoneal LA were 5% and 10.9%, respectively. CONCLUSION • LAs performed by urologists experienced in laparoscopy is safe for the removal of benign and malignant adrenal masses. LA for malignant adrenal tumours should be performed only in high-volume centres by a surgeon performing at least >10 LAs/year.